1995
DOI: 10.1183/09031936.95.08030392
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic analysis and predictive rule for outcome of hospital-treated community-acquired pneumonia

Abstract: P Pr ro og gn no os st ti ic c aan na al ly ys si is s a an nd d p pr re ed di ic ct ti iv ve e r ru ul le e f fo or r o ou ut tc co om me e o of f h ho os sp pi it ta al l--t tr re ea at te ed d c co om mm mu un ni it ty y--a ac cq qu ui ir re ed d p pn ne eu um mo on ni ia a ABSTRACT: In community-acquired pneumonia (CAP) mortality may be reduced by early identification of patients requiring intensive care treatment. The purpose of this study was to determine prognostic factors of outcome in patients with CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
35
0
2

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 11 publications
6
35
0
2
Order By: Relevance
“…These results confirm previous findings [4, 5, 13±15]. Moreover, LDH activity was confirmed as an adverse prognostic factor [5]. Conversely, the parameters diastolic blood pressure #60 mmHg and cardiac frequency $90 beats .…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…These results confirm previous findings [4, 5, 13±15]. Moreover, LDH activity was confirmed as an adverse prognostic factor [5]. Conversely, the parameters diastolic blood pressure #60 mmHg and cardiac frequency $90 beats .…”
Section: Discussionsupporting
confidence: 81%
“…Although BTS rule 2 gave results very similar to the derivation and one validation study (sensitivity 47% and specificity 88% in the present series compared to 39 and 94% in the derivation study [4] and 35 and 89% in the validation study [7], respectively), BTS rule 1 failed to achieve the favourable performances reported in the derivation and two validation studies (sensitivity 65% and specificity 73% compared to 88 and 79% in the derivation study [4] and 70 and 84% [7] as well as 90 and 76% [8] in two validation studies, respectively). As regards the third rule, specificity was close to that reported in the derivation study (80% compared to 77%), but specificity achieved only 47% as compared to 77% in the derivation study [5]. These results suggest that rule 2 is the one that may most appropriately be applied to the elderly.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…With regards an alternative rule proposed by the authors [28], a satisfactory specificity of 80% could be confirmed but only a very limited sensitivity of 47% in this elderly population was found [41].…”
Section: Prognostic Rules For the Individual Hospitalized Patientmentioning
confidence: 61%